1977
DOI: 10.1055/s-0028-1106727
|View full text |Cite
|
Sign up to set email alerts
|

Gefährdung des Menschen durch LCM-Virus-verseuchte Goldhamster

Abstract: Among 291 persons of all age groups from Cologne or Frankfurt and environs who had been in contact with golden hamsters there were 17 (5.8%) with neutralizing antibodies against lymphocytic choriomeningitis (LCM), while such antibodies were present in only 5 (2%) of 251 persons without such contact, the difference between antibody rates representing a probability of error of 5% LCM-virus infections caused by golden hamsters occurred also in city dwellers, younger age groups and more females than has been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Although no cases of PVM due to HIV were identified, some hospital-based studies indicated that meningitis among HIV-positive children was observed to be associated with other bacterial (126) and fungal (127) organisms. The lymphocytic choriomeningitis virus (LCMV) was also suggested in some studies as a causative virus of PVM without concrete confirmatory evidences obtained up-to-date (64,65). Rabies virus was also known to induce VM as a complication of the infection but with much lower frequencies (53,128,129).…”
Section: Other Virusesmentioning
confidence: 99%
“…Although no cases of PVM due to HIV were identified, some hospital-based studies indicated that meningitis among HIV-positive children was observed to be associated with other bacterial (126) and fungal (127) organisms. The lymphocytic choriomeningitis virus (LCMV) was also suggested in some studies as a causative virus of PVM without concrete confirmatory evidences obtained up-to-date (64,65). Rabies virus was also known to induce VM as a complication of the infection but with much lower frequencies (53,128,129).…”
Section: Other Virusesmentioning
confidence: 99%
“…In addition, the Sera of 734 girls in other schools and with no contact were negative (Blechschmidt et al, 1977). A survey in another district on persons of all ages detected a 5.8% incidence of a neutralising antibody response in 291 persons with a history of contact with hamsters and a 2% incidence in 251 with no contact (Ackermann, 1977).…”
Section: Human Infectionsmentioning
confidence: 96%
“…There was no legislation under which these colonies could be destroyed (Forster & Wachendorfer, 1973). Internal hydrocephalus and eye defects at birth in two infants of mothers infected with LCM during pregnancy (Ackermann et al, 1974) and some highly significant data from Lithuania on the correlation of hydrocephalus and eye defects in infants under one year old with LCM antibody in the infants and in the mothers (Sheinbergas, 1976) led to a reiteration of earlier public health authority advice that pregnant women should avoid contact with hamsters (Ackermann, 1977).…”
Section: Human Infectionsmentioning
confidence: 99%